Farming Practices of Rice Farmers in Can-Avid and Dolores, Eastern Samar - Robedizo, Rogelio B. (Annals of Tropical Research, 2015)
The research aimed to account for the technologies practiced by farmers of Can-avid and Dolores, Eastern Samar. These two municipalities are considered as the major rice producing towns of Eastern Samar. It sought to determine the degree of adoption of modern and indigenous rice technologies and to identify the problems met by the farmers in using said technologies. A total of 57 farmers served as respondents. Percentage, means, ranks, and ranges were used to analyse the data. The mean age of the respondents was 54.94 years old with intermediate as the highest educational attainment with 5.43 years of formal schooling. Majority were married with 17.68 average years of farming. The average farm size was 1.26 has. The respondents prepared their rice field by trampling, use of native seeds and by winnowing basket in cleaning the palay with a weighted mean score of 2.04, 2.5, and 2.23 respectively. Results also revealed that 71.05 percent were unsuccessful and 28.93 percent were successful or highly motivated while majority of the modern rice farmers were considered successful or highly motivated (67%). Lack of knowledge and skills about rice farming, farm implements and limited capital, were the problems met by farmers.